An Analysis of Factors that Influence Reading Interest of Grade 8 at SMPN 01 Buay Madang - Shofa, Ghefira Zahira (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
This study aims to analyze the factors influencing the reading interest of grade 8 students at SMPN 01 Buay Madang. Reading interest is a crucial factor in supporting students' academic achievements and personal development. The study utilized observation and interviews as research methods. Observations were conducted during library sessions and breaks, while interviews were carried out with 27 students to explore their reading preferences and challenges. The results revealed that most students preferred fiction books that were engaging, visually appealing, and had exciting plots, avoiding lengthy and dense texts. Additionally, the use of technology significantly influenced reading habits, with many students opting to read on smartphones or gadgets due to easier access and a wider variety of reading materials. However, some students still preferred physical books due to free access. Challenges faced by students included the lack of diverse and appealing books in the library, distractions from social media and games, and limited time for reading. To enhance reading interest, it is recommended to diversify the library collection, make optimal use of technology, and organize interactive reading activities. By addressing these factors, students' reading interest is expected to grow and contribute to their academic success